Helicobacter pylori eradication increases the serum high density lipoprotein cholesterol level in the infected patients with chronic gastritis: A single-center observational study - Iwai, Naoto (PLoS One, 2019)
BACKGROUND: Extra-gastric manifestation of Helicobacter pylori infection involves systemic inflammation, which results in the production of several cytokines. Only a few clinical trials have investigated the effect of H. pylori eradication therapy on lipid metabolism in the infected patients with chronic gastritis. We aimed to evaluate the effect of H. pylori eradication therapy on lipid metabolism in a Japanese population with chronic gastritis. METHODS: One hundred and sixty-three patients with H. pylori-associated chronic gastritis were enrolled in this study between June 2015 and March 2017. They underwent H. pylori eradication therapy; the effects of the therapy were assessed by the urea breath test performed at least 4 weeks after the therapy. After confirming H. pylori eradication, the health screening examination was repeated between May 2016 and August 2018. The clinical parameters were compared before and after the administration of the eradication therapy. RESULTS: The mean age of the enrolled patients was 56.7 years, and the mean follow-up duration was 514.7 days. Weight, body mass index, and obesity index were significantly increased post-eradication therapy compared to those pre-eradication therapy. White blood cell and platelet counts were significantly decreased, and high density lipoprotein cholesterol (HDL) level was significantly increased (P = 0.001), while low density lipoprotein cholesterol (LDL), total cholesterol, and triglycerides levels were not altered significantly. Hence, the LDL/HDL ratio was significantly decreased. CONCLUSIONS: This study reported that H. pylori eradication therapy increase the HDL levels in the infected patients with chronic gastritis. Hence, the LDL/HDL ratio, which is used to evaluate the risk of atherosclerosis, was significantly decreased post-eradication therapy compared to that pre-eradication therapy.